Data Fama : o desempenho dos atletas olímpicos nas redes sociais digitais - Teixeira, Carlos Roberto Gaspar (2017)
This research has sought to analyze how the evolution and the development of the number of followers in the Olympic athletes’ profiles in the social media Facebook, Twitter and Instagram, was influenced by their participation and performance in Rio 2016. For this purpose, was developed a methodology based on the grounded theory, having as proposal a graphical and statistical analysis of the evolution of the followers in the social media of eight Olympic athletes, divided among gold, silver and bronze medalists, besides not medalists. From the results obtained, was developed a theoretical discussion that has allowed to establish some inferences based on the data and concepts explored by other authors. After all the analyzes it was possible to perceive that the participation and performance of the athletes in Rio 2016 had a significant impact on the growth of their social media. However, it was verified the existence of other influential factors besides the presence and success in the Olympic Games, such as economic, mediatic, aesthetic aspects and even the structure of social media platforms analyzed. Instagram was the platform that presented the greatest growth potential, which reinforced the significance of the visual and aesthetic character that sports practice denotes. It has been realized that the Olympic Games, mass media networks, digital social media and athletes are related in such a peculiar and intense way that they can be observed and analyzed as a unique system, where the construction of an image in the digital environment by every athlete characterizes itself as an important asset for the development of their career.